Connexions and condensation in the work of Jimmie Durham - Moiroux, Sophie (Revista de Estudos em Relações Interétnicas | Interethnica, 2014)
The internationally renowned artist Jimmie Durham, who now lives in Europe, elaborated throughout his career a work of contemporary art which is profoundly rooted in his Cherokee culture, while efficiently engaging the art world which gives him an increasingly important place (one of the rare such Amerindian artists). His artwork appears to combine: 1. Contemporary art devises and issues as well as western concepts and viewpoint which he uses and assesses within pieces which are made for a (western) art public, 2. his Cherokee perspective on objects and the world (and 3. his own poetics). The condensation of these two perspectives within art pieces is paradoxical, for they conceive and perceive things and relationships in the world in a priori incompatible ways. Paralleling his work, his own identity or persona is paradoxical, in that on the one hand he defines himself and is considered as an ‘international’ artist, therefore denying the ethnic label which has been applied to him in his early career and which he had to fight, and on the other hand he maintains that his only way to be is as a Cherokee. The continuous colonisation and stereotypification of his peoples in the USA, and their impossibility to be seen as themselves, which the artist feels deeply, cast light on his aim to be a “homeless orphan”. Being truly a Cherokee however does not prevent his being an “international artist”, but rather contributes to it, and vice versa.